Interior design of workplace and performance relationship : private sector corporations in Egypt / Rasha Mahmoud Ali El-Zeiny - Ali El-Zeiny, Rasha Mahmoud (Faculty of Architecture, Planning and Surveying, 2013)
In today’s competitive business environment, corporations can no longer afford to waste the potential of their workforce. There are important factors in the employee’s workplace that influence significantly on their lvel of motivation and performance. The main objective of the study is to understand the relationship between the employees’ performance and their physical work environment. The private sector corporations of Egypt have been chosen as the population for the study. The results of the study show that office design has a substantial impact on the employees’ performance.